1996
DOI: 10.1136/bmj.313.7049.91
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking cessation on plasma ascorbic acid concentration

Abstract: Numerous studies have shown that cigarette smokers have a lower plasma concentration of ascorbic acid than non-smokers, but only a few have considered the antioxidant status of ex-smokers.' We report the first controlled study monitoring the early effect of smoking cessation on the concentration of ascorbic acid in plasma. Subjects, methods, and resultsThe study was conducted in accordance with the Declaration of Helsinki, and the protocol was approved by the local ethics committee. Two hundred volunteers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 4 publications
3
36
0
3
Order By: Relevance
“…In the present study, the plasma concentrations of both total AA and reduced AA were significantly lower in the SM1NNK group compared with the control group (Table III), which is in concordance with the previous human studies showing lower plasma levels of AA in smokers. 44,45 However, the plasma total AA and reduced AA in ferrets with smoke exposure and NNK treatment was not restored to control levels by AOX supplementation. This could be because of either a dose of smoke exposure that overly depleted AA or an insufficient dose of AA, even though ferrets synthesize their own AA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the plasma concentrations of both total AA and reduced AA were significantly lower in the SM1NNK group compared with the control group (Table III), which is in concordance with the previous human studies showing lower plasma levels of AA in smokers. 44,45 However, the plasma total AA and reduced AA in ferrets with smoke exposure and NNK treatment was not restored to control levels by AOX supplementation. This could be because of either a dose of smoke exposure that overly depleted AA or an insufficient dose of AA, even though ferrets synthesize their own AA.…”
Section: Discussionmentioning
confidence: 99%
“…42 In the ATBC trial, subjects were given both b-carotene and vitamin E but without vitamin C. Vitamin C has been shown to protect against in vivo oxidation of lipids and DNA in humans, particularly in persons exposed to enhanced oxidative stress, such as smokers. [43][44][45] The lower vitamin C status of smokers is most likely because of the increased turnover of the vitamin as a result of increased oxidative stress. 46,47 Although plasma AA levels were not reported in the ATBC study, 42 lower levels of plasma AA would be expected among the smokers.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that plasma vitamin C levels are depressed in smokers, and that this relates to smoking itself rather than to depressed dietary intake [26]. Vitamin C is known to block the effect of inflammatory platelet activating factor mimetics, which are activated within minutes of exposure to cigarette smoke in hamsters [27].…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbic acid (AA) is one of the most important cellular antioxidants [1,2] and a valuable biomarker of oxidative stress [3][4][5]. It has been found that AA can inhibit viral infectivity by inactivating viruses and by affecting viral replication.…”
Section: Introductionmentioning
confidence: 99%